A Novel Marine Pathogen Isolated from Wild Cunners (Tautogolabrus adspersus): Comparative Genomics and Transcriptome Profiling of Pseudomonas sp. Strain J380 - Navaneethaiyer Umasuthan; Katherinne Valderrama; Ignacio Vasquez; Cristopher Segovia; Ahmed Hossain; Trung Cao; Hajarooba Gnanagobal; Jennifer Monk; Danny Boyce; Javier Santander (Microorganisms, 2021)
Cunner (Tautogolabrus adspersus) is a cleaner fish being considered for utilized in the North Atlantic salmon (Salmo salar) aquaculture industry to biocontrol sea lice infestations. However, bacterial diseases due to natural infections in wild cunners have yet to be described. This study reports the isolation of Pseudomonas sp. J380 from infected wild cunners and its phenotypic, genomic, and transcriptomic characterization. This Gram-negative motile rod-shaped bacterium showed a mesophilic (4–28 °C) and halotolerant growth. Under iron-limited conditions, Pseudomonas sp. J380 produced pyoverdine-type fluorescent siderophore. Koch’s postulates were verified in wild cunners by intraperitoneally (i.p.) injecting Pseudomonas sp. J380 at 4 × 103, 4 × 105, and 4 × 107 colony forming units (CFU)/dose. Host-range and comparative virulence were also investigated in lumpfish and Atlantic salmon i.p. injected with ~106 CFU/dose. Lumpfish were more susceptible compared to cunners, and Atlantic salmon was resistant to Pseudomonas sp. J380 infection. Cunner tissues were heavily colonized by Pseudomonas sp. J380 compared to lumpfish and Atlantic salmon suggesting that it might be an opportunistic pathogen in cunners. The genome of Pseudomonas sp. J380 was 6.26 megabases (Mb) with a guanine-cytosine (GC) content of 59.7%. Biochemical profiles, as well as comparative and phylogenomic analyses, suggested that Pseudomonas sp. J380 belongs to the P. fluorescens species complex. Transcriptome profiling under iron-limited vs. iron-enriched conditions identified 1159 differentially expressed genes (DEGs). Cellular metabolic processes, such as ribosomal and energy production, and protein synthesis, were impeded by iron limitation. In contrast, genes involved in environmental adaptation mechanisms including two-component systems, histidine catabolism, and redox balance were transcriptionally up-regulated. Furthermore, iron limitation triggered the differential expression of genes encoding proteins associated with iron homeostasis. As the first report on a bacterial infection in cunners, the current study provides an overview of a new marine pathogen, Pseudomonas sp. J380.